The Impact of Accounting Information System Adoption on Financial Transparency and Corporate Governance - Mohammed Al Hasbi (PT. BATARI EDU CALYA, 2025)
The adoption of Accounting Information Systems (AIS) has emerged as a critical determinant of organizational performance, financial transparency, and corporate governance effectiveness in contemporary business environments. This study investigates the impact of AIS adoption on financial transparency and corporate governance practices within the Omani context, a nation actively pursuing digital transformation in its public and private sectors. Employing a quantitative research methodology, this study analyzes data from companies listed on the Muscat Stock Exchange to examine the relationships between AIS implementation, financial reporting quality, and governance mechanisms. The findings reveal that AIS adoption significantly enhances financial transparency through improved information accessibility, accuracy, and timeliness, while simultaneously strengthening corporate governance structures through enhanced accountability and decision-making processes. The study contributes to the existing literature by providing empirical evidence from a Gulf Cooperation Council (GCC) nation undergoing substantial economic diversification and technological modernization. The implications extend to policymakers, corporate managers, and regulatory bodies seeking to leverage technology for improved organizational governance and transparency.